Research of Motion-Compensated Frame Interpolation in Action Image - 赵珑; 周正 (Tongxin xuebao)
in this paper,a new algorithm for motion-compensated inter-frame interpolation is proposed. The motion estimation is combined with the image segmentation on their inherent relation,so that the quality of reconstructed is improved.